2007
DOI: 10.1248/cpb.55.662
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Procedure for Charged Derivatization to Enhance Detection Responses of Steroids in Electrospray Ionization-MS

Abstract: A derivatization procedure has been examined to enhance the electrospray ionization (ESI)-MS detectabilities of steroids that charged derivatization is not suitable for. The derivatization procedure with 2-hydrazinopyridine or isonicotinoyl azide was very effective for the sensitive detection of di-oxosteroids or di-hydroxysteroids, respectively, and the detection limits of the resulting derivatives were as low as about 2 fmol. The derivatives also provided intense characteristic product ions in the MS-MS, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 12 publications
(12 reference statements)
0
45
1
Order By: Relevance
“…group to enhance their mass spectrometric detection (10,(32)(33)(34)(35)(36)(37)(38). We have selected the Girard P derivative that effectively tags a positively charged quaternary nitrogen group to the steroid skeleton.…”
mentioning
confidence: 99%
“…group to enhance their mass spectrometric detection (10,(32)(33)(34)(35)(36)(37)(38). We have selected the Girard P derivative that effectively tags a positively charged quaternary nitrogen group to the steroid skeleton.…”
mentioning
confidence: 99%
“…32) The saliva (200 µL) was deproteinized with acetonitrile, purified using a reversed-phase SPE cartridge, derivatized with a highly proton-affinitive reagent, 2-hydrazinopyridine (HP), 33) and subjected to LC/ MS/MS. Although 17(OH) P has the 3-oxo-4-ene structure, derivatization was employed due to its low salivary level; the HP-derivatization increased the assay sensitivity by 5 times [limit of quantification (LOQ), 5.0 pg/mL] and significantly contributed to reducing the sample volume, which was an important point in developing a method applicable for newborn and child patients.…”
Section: α-Hydroxyprogesteronementioning
confidence: 99%
“…15 The NA derivatives of 3α,5α-Adiol and IS provided their protonated molecules, [M+H] + as the base peak ions. The product ion mass spectrum of the NA derivatives employing the respective [M+H] + as the precursor ions and a 35-eV collision energy showed that a base peak ion was observed at m/z 139.0, which was assigned to the protonated pyridyl carbamic acid (Fig.…”
Section: Esi-ms/ms Of Na Derivativesmentioning
confidence: 99%
“…1). 15 Based on these results, the SRM mode using the [M+H] + and the ion at m/z 139.0 as the precursor and product ions, respectively, was employed in the following studies. When using this mode, the amount of the standard 3α,5α-Adiol derivative giving an S/N of 5 was 2.4 fmol (equivalent to 0.7 pg of intact 3α,5α-Adiol) on column, which was not significantly inferior to that using ECAPCI-MS 8 (1.7 fmol on column).…”
Section: Esi-ms/ms Of Na Derivativesmentioning
confidence: 99%
See 1 more Smart Citation